The Ḫa-BI-ru — Kin or Foe of Israel - Kline, M. G.
1. The Identity of the Ḫa-BI-ru; A: The Word Ḫa-Bl-ru: etymology, SA.GAZ, morphology; В: Critical Survey of the Theories; C: An Ethno-Profession al Interpretation: ethnic unity, professional fraternity, proposed solution.